Efektivitas Model Pembelajaran Kolb dalam Meningkatkan Hasil Belajar Siswa IPS Kelas XI MA Mu’allimin NW Pancor - Muhamad Zaril Gapari (Pendidikan Agama Islam STIT Palapa Nusantara, 2021)
Learning economics is not enough to memorize the material alone, but also need to learn to solve problems on your own in everyday life. This can be achieved if the Kolb model learning is applied in classroom learning activities because Kolb learning can stimulate students' thinking higher in problem-oriented situations. Kolb learning provides opportunities for students to be able to develop observations in solving problems in everyday life. This technique can provoke an independent personality. From this fact, researchers are interested in conducting studies on the application of Kolb's learning model to the ability to solve economic problems of class XI MA students. NW Pancor. This study aims to determine the effectiveness of using the Kolb learning model on learning outcomes (IPS) Economics of class XI students on the accounting information system material of MA. Mu'allimin NW Pancor. The method used in this research is the experimental method. The research design used is by using a Quasi experimental design. The population in this study were all students of class XI MA. Mu'allimin NW Pancor, which consists of 2 classes, namely class XI. IPS.I and XI. IPS. 2. Class XI. IPS.I as the control class and XI. IPS.2 as an experimental class. While the data analysis technique uses the T test. After the data analysis was carried out, the price of tcount = 13.18 and ttable = 2.0042 at the 5% significance level with dk = 56. Because tcount> ttable (13.18> 2.0042) then H0 was rejected and Ha was accepted, which means that learning using the Kolb model is more effective than conventional learning models . Based on the results of testing the hypothesis above, it can be concluded that the use of the Kolb model is effective in improving student learning outcomes in class XI. in MA. Mu'allimin NW Pancor.